The Neutrophil Percentage-to-Albumin Ratio (NPAR) is Associated with In-Hospital Mortality in Patients with Liver Cirrhosis - Lastiana, Ni Made Putri; Mariadi, Ketut; Sindhughosa, Dwijo Anargha; Kumar, Manoj (The Indonesian Society for Digestive Endoscopy, 2025)
Background: Studies show that the Neutrophil Percentage-to-Albumin Ratio (NPAR) predicts mortality in a number of illnesses. On the other hand, there is currently limited clinical support for using NPAR in liver cirrhosis patients. Investigating the associated of NPAR and hospital mortality outcome patients with liver cirrhosis is the goal of this study.Methods: All cirrhosis patients who were admitted to the hospital were included in this retrospective cohort analysis. The percentage of neutrophils and albumin levels on the first day of hospitalization were compared to determine the NPAR. Data were analyzed using the Mann-Whitney test, operating curve (ROC) analysis, and Kaplan-Meier survival curves. P-value 0.05 was considered statistically significant. Results: This study included 98 patients with liver cirrhosis. It was found that NPAR had a high incidence of patient mortality compared to surviving patients who were hospitalised (35.13 vs. 25.33, p 0.001). The median overall survival for all subjects was 10 days, indicating that 50% of the subjects had died within 10 days. According to ROC analysis, NPAR has an ideal cutoff value of 29.63 and can be utilized as a predictor of in-hospital mortality (sensitivity 74.1%, specificity 72.7%, AUC 0.8, p 0.001). Survival analysis stratified by NPAR showed that patients with NPAR ≥ 29.63 had a lower median survival compared to those with NPAR 29.6.Conclusion: In patients with liver cirrhosis, the Neutrophil Percentage-to-Albumin Ratio (NPAR) is a metric that can be used to assess in-hospital mortality outcomes